Yeast cell wall polysaccharides accelerate yet in-feed antibiotic delays intestinal development and maturation via modulating gut microbiome in chickens - Fangshen Guo; Jianing Qiao; Zeqiong Hu; Jia Huang; Ruichen Bi; Waseem Abbas; Wenrui Zhen; Yuming Guo; Zhong Wang (Journal of Animal Science and Biotechnology)
Abstract Background It is important to promote intestinal development and maturation of chicks for feed digestion and utilization, intestinal health, and disease resistance. This study aimed to investigate the effects of dietary yeast cell wall polysaccharides (YCWP) addition on intestinal development and maturation of chickens and its potential action mechanism. Methods 180 one-day-old male Arbor Acres broilers were randomly assigned to three groups containing control (basal diets without any antibiotics or anticoccidial drug), bacitracin methylene disalicylate (BMD)-treated group (50 mg/kg) and YCWP-supplemented group (100 mg/kg). Results Compared with control group, in-feed antibiotic BMD continuous administration significantly decreased crypt depth (d 21) and villus height (d 42) along with mucosal maltase activity (d 42) in the ileum (P < 0.05). Also, BMD markedly downregulated gene expression levels of β-catenin, lysozyme, occludin and FABP-2 (d 21) and innate immune related genes CD83 and MHC-I mRNA levels (d 42, P < 0.05), and decreased goblet cell counts in the ileum of chickens (d 21 and d 42, P < 0.05). While, TLR-2, TLR-6 and iNOS mRNA abundances were notably upregulated by BMD treatment (d 42, P < 0.05). Nevertheless, dietary YCWP addition significantly increased the ratio of villus height to crypt depth (d 21), villus surface area (d 21 and d 42), ileal alkaline phosphatase and maltase activities as well as goblet cell (d 21 and d 42) and IgA-producing plasma cell numbers as compared to BMD treatment (d 21, P < 0.05). YCWP addition also upregulated gene expression levels of Lgr5, Wnt/β-catenin signaling pathway related gene (Wnt3, β-catenin, d 21; β-catenin, d 42), intestinal cells proliferation marker Ki-67 and barrier function related genes (occludin, d 21 and d 42, P < 0.05). Moreover, YCWP significantly increased antigen presenting cell marker related genes (MHC-II, d 21; CD83 and MHC-I, d 42), TLR-1, TLR-2 and TLR-6 mRNA levels (d 21, P < 0.05). Cecal microbiome analysis showed that YCWP addition obviously improved cecal microbial composition, as indicated by increasing relative abundance of Fournierella, Psychrobacter and Ruminiclostridium on d 21, and Alistipes and Lactobacillus on d 42, which were positively related with gut development and maturation related indexes (P < 0.05). Conclusion Collectively, YCWP promoted yet antibiotic BMD delayed intestinal morphological and immunological development linked with modulating gut microbiome in chickens.